Metarhizium robertsii and M. acridum conidia produced on riboflavin-supplemented medium have increased UV-A tolerance and upregulated photoprotection and photoreactivation genes - Huarte Bonnet, Carla (2020)
The aim of this study was to evaluate the effect of riboflavin supplementation of culture medium on conidial UV-A tolerance of M. acridum (Driver & Milner) (Hypocreales: Clavicipitaceae) and M. robertsii (Bischoff, Rehner & Humber) (Hypocreales: Clavicipitaceae). These fungi were produced on culture medium supplemented, or not supplemented, with riboflavin. Relative germination and expression patterns of some photoprotection-related genes were evaluated after irradiating with artificial UV-A, or with filtered solar radiation (> 320 nm; UV-A and visible radiation). M. acridum conidia harvested from riboflavin-supplemented culture medium demonstrated enhanced UV-A tolerance when irradiated with artificial UV-A. Nevertheless, relative germination of conidia of both species produced on riboflavin-supplemented medium and exposed to filtered solar radiation was significantly higher than those produced on medium not supplemented with riboflavin. Riboflavin increased the transcription of photolyases, laccases and polyketide synthase genes. However, each fungal species induced different genes patterns involved in DNA repair and photoprotection. The addition of riboflavin to the substrate used for mass production of Metarhizium spp. and the resulting enhancement of conidial tolerance to solar radiation may improve the effectiveness of these fungi in biological control programs.